Case files. - Toy, Eugene C. (McGraw-Hill Medical, 2013)
Real life cases for the emergency medicine clerkship and shelf-exam. Case Files: Emergency Medicine presents 50 real-life cases that illustrate essential concepts in emergency medicine. Each case includes a complete discussion, clinical pearls, references, definitions of key terms, and USMLE-style review questions. With this system, you'll learn in the context of real patients, rather then merely memorize facts. 60 high-yield emergency medicine cases, each with USMLE-style questions Clinical pearls highlight key concepts Primer on how to approach clinical problems and think like a doctor Proven learning system maximizes your shelf-exam scores.